Evaluation of the distribution of N, P and organic matter in sediment and the pollution status of Lakes in southeastern Hubei Province, China - Xiaowen Lin; Chao Wu; Xiaodong Wu; Xuguang Ge; Zhenni Gao; Xiaoxia Li; Wenting Liu; Shuang Peng (Journal of Freshwater Ecology, 2023)
AbstractEutrophication caused by nutrients and organic matter (OM) pollution is a common problem in the world. The contents of total nitrogen (TN), total phosphorus (TP) and OM in sediments were determined in four typical lakes in southeastern Hubei, China, in the spring of 2019, and their pollution status was evaluated by organic and comprehensive pollution indexes to identify pollution sources and provide specific directions for the pollution control in key areas of the lakes. We found the following: (1) Both nutrients and OM in Cihu Lake and Bao’an Lake were relatively high. Cihu Lake had the highest nutrient and OM in both surface and core sediments. TN, TP and OM in the surface sediments of Cihu Lake reached 700.9 mg/kg, 1668.8 mg/kg and 62.8 kg/g, respectively. The contents of nutrients and OM in Daye Lake and Liangzi Lake were relatively low. OM in these two lakes was significantly lower than that in the Cihu Lake (p < 0.05). (2) The organic pollution and comprehensive pollution revealed that the pollution level of Cihu Lake and Bao’an Lake was moderate to severe. The level of pollution in Daye Lake and Liangzi Lake was mainly mild and moderate. (3) TN pollution was the main factor affecting sediment pollution in the four lakes compared to TP. The risks associated with N pollution merit increased attention. (4) Correlation analysis showed that there was not always a significant correlation between nutrients and OM in surface sediments (p > 0.05). It indicated that the sources of nutrients and OM in sediments were not identical but were affected by many factors. However, the relationship between nutrients and OM was closer in core sediments. In the future, targeted measures should be taken to reduce sediment pollution based on specific pollution sources and pollution conditions in the four lakes, especially Cihu Lake.